Measuring Chemistry Students’ Ability through Entry Test Using the 1-PL IRT Model - Yance Manoppo; Leny Sopia Latuny (Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
Diagnostic instruments for assessing new students' initial abilities often do not meet adequate psychometric criteria. As a result, mapping students' initial abilities is inaccurate and may affect the effectiveness of learning in higher education. This study aims to analyze, evaluate, and interpret the quality of Entry Behavior Test items to produce a valid and reliable instrument. This is a quantitative study with an ex-post facto design. The subjects were 32 new students of the Chemistry Education Study Program at Pattimura University in 2024 who also served as trial subjects by completing 40 multiple-choice questions based on the Computerized Assisted Test (CAT). Data were collected through an objective test validated by three experts. Data analysis was performed using Classical Test Theory (CTT) through the Iteman 3.0 program and Item Response Theory (IRT) with a 1-parameter logistic model with Bilog-MG 3.0. The results showed that the instrument had fairly good reliability, but some items had suboptimal levels of difficulty and discrimination, requiring revision. In conclusion, the Entry Behavior Test instrument is quite suitable for use, but still needs improvement to increase the accuracy of measuring students' initial abilities. The implication of this research is the need to develop more valid, reliable, and adaptive diagnostic instruments to support the quality of assessment in higher education.